Comment. Modernity, identity and utopia in Latin America, Aníbal Quijano - López Córdova, Dania (2022)
This commentary seeks to present some key elements of Modernidad, Identidad y Utopía en América Latina by Anibal Quijano, considered a classic of social thought. It is an acute reflection against the current, since in the midst of the debates on postmodernity, the author maintains that the liberating promises of modernity should not be renounced, this on condition of problematizing its eurocentric history, recognizing the contributions of other rationalities and not abandon the question of power. Thus, Quijano presents various intuitions that prefigure what will be his theoretical perspective of the Des/Coloniality of power and anticipate the deployment of the proposals like Buenos vivires in Latin America.